Interferometric fibre optic sensors incorporating photonic crystal fibre, for the measurement of strain and load - Manders, Mark (Cranfield University, 2016)
Strain sensing is important in numerous fields such as: structural health monitoring [1], manufacture of composites [2], and civil engineering [3]. For many of these fields fibre optic based sensors have been utilised due to their numerous advantages, that will be described in Chapter 2. In this thesis I will described the production of three new fibre optic based strain sensors: a microcavity based in-fibre Fabry-Perot etalon (Chapter 4), a birefringent photonic crystal fibre (PM-PCF) based Michleson-interferometer (Chapter 5), and a polarisation maintaining fibre (PMF) based Michleson-interferometer (Chapter 6). In this chapter we will describe the aim of this work, the novelty of this work, and how this work is presented in this thesis.